Improvement of Engine Room Watchkeeping Activity on Zada Hela Liveaboard - I Made Aditya Nugraha; Febi Luthfiani; Yosep Sulistio Was (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2023)
Zada Hela Liveaboard is one of the tourist ships that serve shipping activities in East Nusa Tenggara, especially in the Labuan Bajo area. This ship is equipped with facilities that greatly pamper the passengers during their cruise activities. To be able to support and provide a sense of security and comfort to the passengers, good engine room watchkeeping activities are needed, but some shortcomings were found. The deficiencies in watchkeeping activities were then analyzed by observation and interviews with 6 respondents to make improvements. Improvement of engine room watchkeeping activities can finally be done by making a watchkeeping schedule, logbooks, and adding 3 assistant engineers. These items will be very helpful in checking and knowing the condition of the engine on the ship. The addition of 3 assistant engineers to assist the chief engineer is also very necessary. This is in accordance with STCW and to provide a longer rest time, so as to prevent fatigue when doing watchkeeping in the engine room.